Diketopiperazine and alloxazine alkaloids from the antarctic bacteria, Pseudorhodobacter psychrotolerans sp. nov. (August 2019) - Youn, Ui Joung; Lee, Jun Hyuk; Han, Se Jong
Abstract: Chemical investigation of the ethyl acetate extract of the Antarctic bacteria, Pseudorhodobacter psychrotolerans sp. nov. led to the isolation of five diketopiperazines (1 –5 ), an alloxazine (6 ), p -hydroxybenzoic acid (7 ), and 2-methylbutanedioic acid (8 ). The structures of these compounds were confirmed by 1D and 2D-NMR and MS experiments, as well as by comparison with published values. This is the first phytochemical study of Pseudorhodobacter psychrotolerans sp. nov. Furthermore, all the compounds have been isolated for the first time from the genus Pseudorhodobacter and the family Rhodobacteraceae. The chemotaxonomic significance of the isolated compounds is discussed. Highlights: Eight compounds (1 -8 ) were isolated from the Antarctic bacteria, Pseudorhodobacter psychrotolerans sp. nov. All the compounds were isolated for the first time from the genus Pseudorhodobacter and the family Rhodobacteraceae. The chemotaxonomic significance of the isolates was discussed in this study.